1999
DOI: 10.1097/00003246-199912000-00035
|View full text |Cite
|
Sign up to set email alerts
|

Successful resuscitation of a verapamil-intoxicated patient with percutaneous cardiopulmonary bypass

Abstract: In patients with cardiac arrest attributable to massive verapamil overdose, percutaneous extracorporeal cardiopulmonary bypass can provide adequate tissue perfusion and sufficient cerebral oxygen supply until the drug level is reduced and restoration of spontaneous circulation can be achieved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(35 citation statements)
references
References 18 publications
2
32
0
1
Order By: Relevance
“…These early studies showed improved mortality in models of lidocaine and amitriptyline poisoning [11,12]. Numerous human case reports and case series have since shown favorable outcomes although ECMO has been primarily used in poisonings involving pharmaceuticals such as antidysrhythmics and other cardiovascular medications, as well as tricyclic antidepressants [13][14][15][16][17][18][19][20][21][22][23][24][25]. Many of the pharmaceutical exposures in our cohort were similar to cases reported in the literature with most leading to cardiotoxicity or hemodynamic collapse (flecainide, diphenhydramine, and verapamil).…”
Section: Discussionmentioning
confidence: 99%
“…These early studies showed improved mortality in models of lidocaine and amitriptyline poisoning [11,12]. Numerous human case reports and case series have since shown favorable outcomes although ECMO has been primarily used in poisonings involving pharmaceuticals such as antidysrhythmics and other cardiovascular medications, as well as tricyclic antidepressants [13][14][15][16][17][18][19][20][21][22][23][24][25]. Many of the pharmaceutical exposures in our cohort were similar to cases reported in the literature with most leading to cardiotoxicity or hemodynamic collapse (flecainide, diphenhydramine, and verapamil).…”
Section: Discussionmentioning
confidence: 99%
“…Other treatments that were mentioned in the articles as being potentially beneficial but that would not likely be available to, or practicable for, U.S. out-ofhospital personnel are not listed in the table. These include dexamethasone (81), methylscopolamine (91), metaproterenol (66,139), 4-aminopyridine (134), amrinone (96,138), angiotensin II (25), theophylline (139), enoxamine (73), and vasopressin (112). General supportive care measures (e.g., airway management measures, fluids, anticonvulsants, bicarbonate) might have been beneficial in some cases but were difficult to evaluate and are not specifically addressed in the table or this summary.…”
Section: Other Treatmentsmentioning
confidence: 99%
“…Extracorporeal life support has shown a good survival outcome in at least one case report of verapamil toxicity83 and three observational studies that also involve other cardiotoxic drugs 84–86. Unfortunately, such an invasive procedure is not without side effects.…”
Section: Discussionmentioning
confidence: 99%